2022
DOI: 10.1136/bmj-2022-071932
|View full text |Cite
|
Sign up to set email alerts
|

Comparative effectiveness of sotrovimab and molnupiravir for prevention of severe covid-19 outcomes in patients in the community: observational cohort study with the OpenSAFELY platform

Abstract: Objective To compare the effectiveness of sotrovimab (a neutralising monoclonal antibody) with molnupiravir (an antiviral) in preventing severe outcomes of covid-19 in adult patients infected with SARS-CoV-2 in the community and at high risk of severe outcomes from covid-19. Design Observational cohort study with the OpenSAFELY platform. Setting With the approval of NHS England, a real world cohort study was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
103
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 64 publications
(113 citation statements)
references
References 25 publications
(53 reference statements)
2
103
1
Order By: Relevance
“…The copyright holder for this this version posted December 30, 2022. ; https://doi.org/10.1101/2022.12.30.22284063 doi: medRxiv preprint with similar demographics and again among patients on kidney replacement therapy covering BA.2 predominant period in the UK and found sotrovimab to be effective throughout BA.1, BA. 2 and BA.4/5 predominance [20].…”
Section: Discussionmentioning
confidence: 94%
“…The copyright holder for this this version posted December 30, 2022. ; https://doi.org/10.1101/2022.12.30.22284063 doi: medRxiv preprint with similar demographics and again among patients on kidney replacement therapy covering BA.2 predominant period in the UK and found sotrovimab to be effective throughout BA.1, BA. 2 and BA.4/5 predominance [20].…”
Section: Discussionmentioning
confidence: 94%
“…In a real-world study conducted in England among high-risk nonhospitalized patients, treatment with sotrovimab was associated with 46% lower risk [hazard ratio (HR) 0.54, 95% CI 0.33–0.88] of 28-day hospitalization or death during the Omicron BA.1 period (16 December 2021–10 February 2022) and 56% lower risk (HR 0.44, 95% CI 0.27–0.71) during the Omicron BA.2 period (16 February 2022–1 May 2022) compared with treatment with molnupiravir [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…30 The results of this study compliment other recent real-word studies on early treatments for COVID-19 in the UK. [31][32][33] For example, the findings of a recent publication on the comparative effectiveness of sotrovimab versus molnupiravir in England, conducted using the OpenSAFELY platform, showed that sotrovimab treatment was associated with a significant reduction in risk of severe COVID-19 outcomes in comparison to treatment with molnupiravir during BA.1 (primary analysis) and BA.2 (exploratory analysis) predominance. 31 Moreover, sotrovimab was found to offer a similar level of protection against disease progression in patients with COVID-19 infected with the Omicron BA.1 and BA.2 subvariants.…”
Section: Discussionmentioning
confidence: 99%
“…[31][32][33] For example, the findings of a recent publication on the comparative effectiveness of sotrovimab versus molnupiravir in England, conducted using the OpenSAFELY platform, showed that sotrovimab treatment was associated with a significant reduction in risk of severe COVID-19 outcomes in comparison to treatment with molnupiravir during BA.1 (primary analysis) and BA.2 (exploratory analysis) predominance. 31 Moreover, sotrovimab was found to offer a similar level of protection against disease progression in patients with COVID-19 infected with the Omicron BA.1 and BA.2 subvariants. 32 Similarly, in an observational study in the US, treatment with sotrovimab was associated with a reduced risk of all-cause hospitalisation and mortality during the predominance of early Omicron variants.…”
Section: Discussionmentioning
confidence: 99%